Prediksi Rasio Profitabilitas Bank Umum Syariah yang Terdaftar ISSI: Pendekatan Tren Kuadratik - Putri, Filda Felisa; Dahruji, Dahruji; Rahman, Taufiqur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to predict the profitability levels of Islamic Commercial Banks listed on the Indonesian Sharia Stock Index (ISSI) using a quadratic trend approach. The data sources are derived from the annual financial reports of PT Bank Syariah Indonesia Tbk, PT Bank Panin Dubai Syariah Tbk, PT Bank Aladin Syariah Tbk, and PT Bank BTPN Syariah Tbk spanning from 2019 to 2023. The approach applied in this analysis uses quadratic trend to predict Return on Assets and Return on Equity from 2024 to 2028. The forecasting results indicate a significant upward trend for both profitability ratios. ROA is expected to increase from 5.42 in 2024 to 12.98 in 2028, while ROE is projected to rise from 21.96 to 82,8 during the same period. This study concludes that Islamic Commercial Banks show very positive potential financial performance, with stable increases in ROA and ROE, indicating strong growth potential and significant improvement in financial performance in the coming years. These findings provide important insights that investors can consider when making investment decisions in publicly listed Islamic Commercial Banks in the Indonesian Islamic banking sector.